Stroke and myocardial infarction prevention with GLP1 analogues in high or very-high cardiovascular risk diabetic patients. (25th November 2020) - Cazorla-Morallon, D; Cordero, A; Pomares Varo, A; Torroba Balmori, G; Moreno Garcia, M.J; Martinez Rey-Ranal, E; Bertomeu-Gonzalez, V; Zuazola, P
Abstract: Background: Patients with established cardiovascular disease have an increased risk of stroke, even in the absence of atrial fibrillation. Several trials have analysed the effect of glucagon-like peptide-1 receptor (GLP1) analogues on cardiovascular events in patients with high cardiovascular disease. Methods: We performed a metanalysis with all randomized clinical trial that compared a GLP1 analogue vs. placebo. Primary endpoint was stroke incidence, including ischemic and haemorrhagic aetiology, assessed by fixed-effect model. Results: We identified 7 trials that compared a GLP analogue (albiglutide, dulaglutide, exenatide, liraglutide, lixinatide or semaglutide). A total of 56, 004 patients were included in the analysis, 27977 treated with a GLP1 analogue. Mean age of the patients was 63.9 (2.1) years, 25, 398 (45.4%) patients had cardiovascular disease. A total of 1, 568 strokes were reported, 711 in patients receiving a GLP analogue and 857 in control arm; treatment with a GLP1 analogue reduced the incidence of stroke by 147% (RR: 0.83, 95% CI 0.75–0.92; p<0.001). No heterogeneity between trials was observed (p=0.835). Globally, treatment with GPL1 analogues reduced the incidence of stroke or myocardial infarction by 11% (RR: 0.89, 95% CI 0.84–0.94; p<0.01) A total of 3, 192 cases of myocardial infarction were reported: 1, 524 in patients treated with GLP1 analogues and 1, 668 with placebo. Treatment with GLP1 analogues reduce the incidence of myocardial infarction by 8% (RR: 0.92, 95% CI 0.86–0.98; p=0.010) Conclusions: Treatment with a GLP1 analogue reduced the incidence of stroke by 17% and myocardial infarction by 8%, in different trials involving high or very-high risk patients with diabetes. Funding Acknowledgement: Type of funding source: None